The role of energy management technologies for cyber resilient smart homes in sustainable urban development - Um-e-Habiba; Ijaz Ahmed; Mohammed Alqahtani; Muhammad Asif; Muhammad Khalid (Energy Strategy Reviews)
Technology is essential in creating sustainable cities. Home automation is a branch of Internet of Things (IoT)-based automation, enhancing our lifestyle by automating everyday tasks. People are currently incorporating this concept to create intelligent cities. Smart home (SH) automation has employed a variety of methods and procedures. In order to optimize the system’s performance, it is crucial to gain a thorough understanding of it. This study investigates into the ways that the implementation of SH automation can aid in the development of sustainable cities by examining various approaches. This study examines into the ways in which technology can tackle the technical hurdles of handling large volumes of data and improving a city’s overall efficiency. Furthermore, the review explores innovative technological concepts that have the potential to enhance the intelligence of cities. These findings offer valuable insights for policymakers, legislators, academic scholars, and technologists in shaping future research directions and enhancing these technologies for the betterment of humanity and the development of sustainability.